COMPOSITE MATERIALS AS INOVATING FEATURE IN MECHANICS OF MATERIALS - MURČINKOVÁ, Zuzana (Trends in education, 2010)
The paper dealt with integration of composite materials behaviour principles into classical teaching of subject Mechanics of materials. Such integration provides innovative feature for subject. One of basic assumptions in calculations is that material is homogenise and isotropic. In case of composites, the basic assumption is not fulfilled. Anisotropy of composites introduces larger applications or changing the conventional thinking of calculations and designing.
Keywords: composite material; anisotropy; calculation; computer simulation.